Book Review: Great help for novice GT researchers - Tove Giske (Grounded Theory Review: An International Journal, 2016)
The authors’ main purpose of the book is to provide practical guidance for novice researchers using classic grounded theory (GT) while remaining as true as possible to Glaser’s and Strauss’ thoughts. In addition, they want to show that GT is much more than a qualitative research methodology; throughout the book, the authors provide examples of how qualitative and quantitative data can be used to develop substantive and formal grounded theory.